(untitled) (Journal of Applied Learning and Teaching, 2024)
Since the COVID-19 pandemic, the migration to teaching and learning using technology-enhanced activities has accelerated, especially in higher education. With this shift, teaching staff are required to either use commercial products or develop individual online teaching resources. However, commercial resources come with a cost, may not exist for the required topic(s), or may not suit the teaching requirements of a particular student cohort. In addition, it is common for most academics to have limited to no experience in making educationally effective interactive technology-enhanced learning resources. Thus, generated materials may lack critical features that maximise student learning experiences. To address this problem, we distilled over a decade’s experience designing and implementing online educational materials for tertiary STEM and Medical and Health Science courses to develop a micro-model taxonomy. Our proposed model builds on the ASSURE and Design Thinking Macro models providing a detailed breakdown of important factors and justifications, where possible, for their inclusion in all resources. While our approach is based on the Articulate Storyline software platform, the taxonomy is software agnostic and can be applied to the design of any technology-enhanced learning resource for any course. Potential pitfalls and areas for enhancing student learning are also addressed.